NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB QOMI’ AL-THUGHYAN - Asyiqul Mujahadah; Anwar Sa’dullah; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Islamic education essentially takes place in a process. The process is in the form of transforming moral values into everyday behavior. In addition, morality is proof that someone has a personality, good behavior, as taught by the Prophet Muhammad, as a human being sent to perfect morality on earth. The purpose of this study is 1) to know what morality is towards Allah SWT. and the Prophet SAW. in the book Qomi 'Al-Thugyan, and 2) to know the morality of oneself, the third) knows akhak to the environment, which in this case the author classifies into two, namely: Morals towards parents, and morals towards others. The relationship between morals to others is a lot, including morals towards neighbors, morals towards leaders, morals of a superior to subordinates, also morals of a subordinate to his boss, morals towards people who are smaller, morals towards older people. With this research, we are expected to all be able to follow the commands of Allah SWT. and also following the teachings of the Prophet Muhammad. so that the creation of a harmonious life order, both towards the relationship with God and His Messenger, is also a relationship between humans.